The Effect of Overconfidence and Experience on Belief Adjustment Model in Investment Judgement - Almilia, Luciana Spica; Wulanditya, Putri (Universitas Prasetiya Mulya, 2016)
This study examines the effect overconfidence and experience on increasing or reducing the information order effect in investment decision making. Subject criteria in this research are: professional investor (who having knowledge and experience in the field of investment and stock market) and nonprofessional investor (who having knowledge in the field of investment and stock market). Based on the subject criteria, then subjects in this research include: accounting students, capital market and investor. This research is using experimental method of 2 x 2 (between subjects). The researcher in conducting this experimental research is using web based. The characteristic of individual (high confidence and low confidence) is measured by calibration test. Independent variable used in this research consist of 2 active independent variables (manipulated) which are as the followings: (1) Pattern of information presentation (step by step and end of sequence); and (2) Presentation order (good news – bad news or bad news – good news). Dependent variable in this research is a revision of investment decision done by research subject. Participants in this study were 78 nonprofessional investor and 48 professional investors. The research result is consistent with that predicted that individuals who have a high level of confidence that will tend to ignore the information available, the impact on individuals with a high level of confidence will be spared from the effects of the information sequence.